Fracture Treatment using External Skeletal Fixation (ESF) Method in Golden Hornbill (Rhyticeros undulates) - Rahman, Muhammad Noor; Apritya, Desty; Sari, Dian Ayu Kartika (Universitas Airlangga, 2023)
A golden hornbill (Rhyticeros undulates), male, one year old, reported clinical signs that one of the legs was limping. Based on the X-ray examination reported that there was a fracture of the tibiotarsus bone. External skeletal fixation (ESF) was performed for connecting bones using size 1,2 pins. The general anesthetic used was a combination of zolazepam-tiletamine at a dose of 5 mg/kgBW and given 0,1 mg/kgBW meloxicam. Postoperative therapy includes enrofloxacin at a dose of 15 mg/kg intramuscularly, dexamethasone at a dose of 0,2 mg/kgBW intramuscularly, and Osteocare® at a dose of 5 mg/kg orally. After five days postoperatively, the bird's condition had returned to normal. It can be concluded that fractures in birds can be treated using the ESF method.